HEURISTIC OPTIMIZATION FOR DEMAND SIDE MANAGEMENT IN SMART GRID - MANOJ D. PATIL; ANAND BHUPAL KUMBHAR (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Demand side management (DSM) is major aspects in a smart grid which allows customers to take decision based on information for their consumed energy, which also helps in reduction of peak load demand for the energy producers which enables the reshaping of the load profile. Advantage of doing this will increase the sustainability of the smart grid and benefits in reduction of operational cost and lower production of green house gases. The various strategies available for demand side management uses an traditional energy management system which possesses and certain disadvantages related to algorithms. Moreover the existing strategies can handle only a limited number of controllable loads with limited types. In this paper presentation related to demand side management is implemented and explained for future grid, termed as smart grid. Load shifting technique before 24 hour was implemented and explained in this paper. Heuristic evolutionary algorithm(EA) is used for solving the minimization problem.